Review of the Strepsiptera fauna of the Nordic countries with the description of two new species of Stylops Kirby (Stylopidae) - Lähteenaro, Meri; Benda, Daniel; Covelli, María Alejandra Álvarez; Forshage, Mattias; Hovmöller, Rasmus; Nylander, Johan A. A.; Straka, Jakub; Bergsten, Johannes (Zootaxa, 2026)
Twisted-winged parasites (Strepsiptera) is a small insect order with around 610 species worldwide and whose members are obligate parasites of other insects. While recent advances in molecular methods have significantly improved our understanding of the species diversity, there is no review of Strepsiptera diversity from the Nordic countries that fully reflect the current state of taxonomic knowledge. Here we revise the Nordic Strepsiptera fauna, present an updated and annotated checklist of species, including new distribution data and host associations based on new records from museums, private collectors, previous publications, and databases. We describe two new species of Stylops (Strepsiptera: Stylopidae) from the Nordic countries, Stylops sapmiensis Lähteenaro & Bergsten, sp. nov. and Stylops serotinus Lähteenaro & Straka, sp. nov., supported by molecular, morphological, and host-use data. A key to genera of Nordic Strepsiptera based on males and to species based on females is provided together with distribution maps of known species.